The countercyclical benefits of regulatory costs - Alexander Mechanick; Jacob P. Weber (Federal Reserve Bank of New York, 2024)
Legal academics, journalists, and senior executive branch officials alike have assumed that the cost of imposing new regulatory requirements is higher in severe recessions that drive the central bank's policy rate to zero than in other times. This is not correct; the aggregate output costs of regulatory requirements decrease, not increase, in such recessions. This article is the first to analyze how this effect arises, drawing on both conventional macroeconomic models and empirical findings from the econometrics literature. Scholars and policymakers have likely missed the countercyclical benefits of regulatory costs because of informal, ad hoc macroeconomic assumptions embedded in regulatory analysis.
Keywords: E02; E6; K2; K3; 330; law and economics; law and macroeconomics; zero lower bound